Korea-China Relations in History and Contemporary Implications - Chan, Robert Kong (Critical Studies of the Asia-Pacific,, 2018)
This book examines the complex relations between Joseon Korea (1392-1910) and Ming/Qing China in history, and reveals their contemporary implications for the nature of a China-dominated order in East Asia and the relations between China and the middle powers in the region. Instead of relying on the works that offer over-generalized conclusions based on information drawn from secondary sources, this book provides a much more nuanced account of the Koreans' experience of managing their relations with the great powers by analyzing the first-hand evidence documented by the Joseon historiographers related to the major events in Joseon-Ming relations, Joseon's response to power transition from Ming to Qing, and Joseon-Qing relations. In East Asia today where the middle powers are facing the rise of China and a trilateral dilemma as a result of the Sino-US rivalry in the region, what history can tell us is of significant value to scholars, policy advisers, and policymakers.